Physiological modifications of seston in response to physicochemical gradients within Lake Superior. (1st May 2014) - Bellinger, Brent J.; Van Mooy, Benjamin A. S.; Cotner, James B.; Fredricks, Helen F.; Benitez-Nelson, Claudia R.; Thompson, Jo; Cotter, Anne; Knuth, Michael L.; Godwin, Casey M.
Abstract : In September 2011, we investigated the distribution and composition of dissolved and particulate phosphorus (P) pools throughout Lake Superior, a large P‐limited freshwater ecosystem. Average seston particulate P (PP) concentrations in the deep chlorophyll maximum (DCM; 85 ± 28 nmol L −1 ) were significantly greater than in the epilimnion (63 ± 22 nmol L −1 ). In contrast, average particulate organic carbon (POC) : PP (mol : mol) ratios showed the opposite pattern (DCM = 303 : 1 vs. epilimnion = 455 : 1). Mean seston nucleic acid—P concentrations were invariant between the epilimnetic (23 ± 18 nmol L −1 ) and DCM (26 ± 18 nmol L −1 ) layers, but significantly greater concentrations of intact polar membrane—derived phospholipids were found in the DCM (6 ± 2 nmol L −1 ) relative to the epilimnion (4 ± 2 nmol L −1 ). Phospholipids were a minor proportion of PP (7–14%) and total membrane lipids (< 30%). Rather, our results suggest that microbial flora of Lake Superior substituted non‐phosphorus lipids for phospholipids. In the nitrogen (N)—rich waters, N‐based betaine lipids dominated (39–42%) the lipid pool, and concentrations were significantly greater in the P‐poor epilimnetic seston. Sulfolipids were also abundant and significantly greater in the epilimnion (7 ± 2 nmol L −1 ) than in the DCM (4 ± 2 nmol L −1 ), despite low sulfate concentrations relative to marine environments. Our results demonstrate for the first time the importance of plankton producing non‐phosphorus lipids for phospholipids as a strategy for reducing cellular P inventories in lacustrine regimes.